Cinnamon in Anticancer Armamentarium: A Molecular Approach - Anindita Dutta; Anindita Chakraborty (Journal of Toxicology)
In recent years, natural bioactive components draw a major attention for their potent anticarcinogenic activity. Cinnamon, one of the traditional spices, most frequently used in almost every household of tropical countries has got enormous efficacy to combat cancer. Cinnamon as a whole and/or its active components exhibited significant antineoplastic activity in different types of cancer. This review has been carried out to elicit the molecular mechanisms of action of cinnamon and its components on oncogenic regulators and related pathways. Web sites of Google Scholar, Medline, and PubMed were searched for articles written in English and published in peer-reviewed journals from 2003 to 2017. The anticarcinogenic potential of cinnamon varies with the type of cancer and also depends on the administered active compound individually or in combination with some chemicals or even extract of cinnamon as a whole. Some of its active components exert chemosensitization of well-known anticancer drugs. These outstanding properties of this spice necessitate its incorporation in both pharmaceuticals and nutraceuticals to explore possibilities of formulation of novel drug from this spice for treatment and prevention strategy of cancer.